Anxiety and depression mediate the relationship between digestive tract conditions and oral health-related quality of life in orthodontic patients - Tian, Xue; Li, Yuan-hong; Deng, Lan-zhi; Han, Wen-ze; Pu, Dan; Han, Xiang-long; Du, Shu-fang; Deng, Wei (Frontiers in Psychology, 2022)
Background: Anxiety and depression are common psychological problems in orthodontic patients whose diet habits and oral health status change frequently during treatment. However, relationships between anxiety and depression, digestive tract condition and impaired oral health-related quality of life remain unknown. Method: In the current study, clinical assessments, including anxiety, depression, digestive tract condition, and oral health-related quality of life, were collected from 769 outpatients in the orthodontic department using three self-reporting questionnaires. Correlation analysis was used to investigate the relationships among different clinical assessments. A chained mediation analysis model was further conducted to explore the direct and indirect effects of these various clinical factors. Results: Changes in digestive tract condition were positively correlated with psychological status and oral health-related quality of life. Anxiety and depression partially mediated the relationship between them, and the indirect effect was 0.68 (30%), of which the mediation effect of anxiety accounted for 56%. Conclusion: Anxiety and depression mediate the relationship between gastrointestinal conditions and oral health. In particular anxiety seems to play a significant mediating role. Our findings indicated that psychological status must be paid more attention to in future clinical practices and supervision for digestive tract symptoms of orthodontic patients.